THE EFFECT OF STARCHITECT’S DESIGN ON HOUSING IMAGE ACCORDING TO RESIDENTS' PERCEPTION - Gentina Pratama Putra; Rona Fika Jamila (MODUL, 2022)
The development of residential real estate in Indonesia continues to grow. Although it cannot be denied that the current global economic recession affect the property business, housing development must continue to grow in order to accommodate the population demand. The recent economic conditions make housing developers have to make various innovations for convincing the public to buy their housing units. One of the innovations carried out is to recruit famous architects to collaborate in designing their housing. There are those who collaborate to design housing units in their housing clusters, but there are also those who collaborate since the creation of masterpaln to housing units. Of course, with the hope of cooperating with famous architects will be able to make their housing more pretentious, preferred by consumers, and ultimately bought by consumers.While on the community side, what do they expect by buying a house in housing designed by a well-known architect? Is it because of prestige, is it because of other things? This phenomenon is what makes researchers interested in finding out what the influence of a famous architect on the image of a housing in the eyes of the public.The purpose of this study was to determine the effect of the design of starchitect.